Suppression of Cell Tumorigenicity by Non-neural Pro-differentiation Factors via Inhibition of Neural Property in Tumorigenic Cells - Yang, Xiaoli; Cao, Ning; Chen, Lu; Liu, Lin; Zhang, Min; Cao, Ying (Frontiers in Cell and Developmental Biology, 2021)
Our studies have demonstrated that cell tumorigenicity and pluripotent differentiation potential stem from neural stemness or a neural ground state, which is defined by a regulatory network of higher levels of machineries for basic cell physiological functions, including cell cycle, ribosome biogenesis, protein translation, spliceosome, epigenetic modification factors, reprogramming factors, etc., in addition to the neural stemness specific factors. These machineries and neural stemness factors mostly play cancer-promoting roles. It can be deduced that differentiation requires the repression of neural ground state and causes the reduction or loss of neural ground state and thus tumorigenicity in tumorigenic cells. Formerly, we showed that neuronal differentiation led to reduced tumorigenicity in tumorigenic cells. In the present study, we show that non-neural pro-differentiation factors, such as GATA3, HNF4A, HHEX, and FOXA3 that specify mesodermal or/and endodermal tissues during vertebrate embryogenesis, suppress tumorigenicity via repression of neural stemness and promotion of non-neural property in tumorigenic cells. Mechanistically, these transcription factors repress the transcription of neural enriched genes and meanwhile activate genes that specify non-neural properties via direct binding to the promoters of these genes. We also show that combined expression of HHEX and FOXA3 suppresses tumorigenesis effectively in the AOM/DSS model of colitis-associated cancer. We suggest that targeting the property of neural stemness could be an effective strategy for cancer therapy.